Peran Gap Junction pada Patofisiologi Fibrilasi Atrial - Alexander Edo Tondas; Yoga Yuniadi (Jurnal Kardiologi Indonesia, 2010)
Initiation of atrial fibrillation (AF) occurred when there is a combination of triggering factors (mainly originated from thoracic veins) and arrhytmogenic substrate, such as : reduction of effective refractory period (ERP), increase in refractory spatial dispersion, or abnormal atrial impulse conduction. Atrial fibrillation has an ability to maintain its own progression, so called ‘AF begets AF’. Prologed AF episodes will lead to structural and electrical remodeling, making the patient prone to the recurrent and sustained AF. Structural remodeling, detected in the late phase, involve changes in mitochodrial size, disorder of sarcoplasmic reticulum in subcellular level, and myocardial cell hypertrophy, fiber disarray and elevated collagen deposition in the tissue level. Meanwhile, electrical remodeling of AF will cause delayed effective refractory period, promoting reentry mechanisms. Changes in gap junction regulation and distribution has been noted as part of this remodeling process. Mutation of connexin40 gene, a component protein of gap junction, also has a role in some cases of lone AF.